Impact of educational intervention regarding oral rehydration solution and zinc for management of diarrhoea among mothers of urban slums of Ahmedabad city, Gujarat, India: an interventional study - Chaudhari, Chintu C.; Gunjana, Geet; Thakor, Nilesh (International Journal of Research in Medical Sciences, 2016)
Background: Diarrhoea is one of the leading causes of morbidity and mortality among under-five children. Timely management of the children with oral rehydration solution (ORS) has substantially declined the mortality and morbidity from acute infectious diarrhea. The use of ORS largely depends on the level of knowledge and attitude of mothers. Mothers’ knowledge about diarrhoea can be improved through educational interventions. The objective of the study was to assess knowledge of mothers of urban slums of Ahmedabad city of Gujarat regarding ORS and Zinc for management of diarrhoea before and after training. Methods: This Interventional study was conducted among purposively selected 100 mothers of under five children of urban slums of Ahmedabad city of Gujarat, India during June to August 2011. After taking verbal consent, baseline knowledge of mothers regarding ORS and Zinc for management of diarrhoea was assessed by pre-designed, pre-tested and semi structured questionnaire. Single educational interventional training for 45 minutes was given to selected mothers Pre and post training assessment was done by scoring method and also mean, standard deviation, Wilcoxon sign rank test were applied. Results: Almost 83% of the mothers could define diarrhoea as the passage of watery stools three or more times a day, this knowledge was significantly increased to 100% after the training. Baseline knowledge of the mothers regarding causes of diarrhoea in children, signs and symptoms of dehydration in children, Correct method of preparation of ORS and importance of zinc therapy along with ORS was 4%, 22%, 39% and 26% respectively which was significantly increased to 73%, 90%, 89% and 76% respectively after the intervention. Conclusions: Knowledge of the mothers of under-five children regarding causes of diarrhoea, signs and symptoms of diarrhoea, correct method of preparation of ORS and importance of zinc therapy along with ORS has been significantly increased after intervention.